Raw material loss evaluation: a proposal to improve a bakery process - Carvalho, Flavio Lucio Santos de; Leite Junior, Clério Pereira (Brazilian Journal of Production Engineering, 2022)
The increased competitiveness among the companies in the market causes organizations to increasingly seek ways to increase their productivity and minimize the potential for waste of their resources. Thereby it becomes fundamental knowledge of all the activities that add or not value the process and the product. One of the fundamental ways to improve processes and increase the revenues is the elimination or reduction of waste of resources. In this way, the present work shows its objective being a suggestion of proposal for improvement of the productive process of a bakery located in a city of the northern region of Espirito Santo State. To achieve this success in the research, several data were collected from the company’s production processes such as monthly production, consumption of resources and costs associated with production. Subsequently, the application of the VSM tools and the Cause and Effect Diagram allowed for a better analysis of the process and obtaining a diagnosis of the real and current situation for the visualization and quantification of the same. Finally, the suggestion proposal for the improvement of the process was carried out aiming at reducing the consumption of wheat, a resource defined as being more representative during the production process, and a better efficiency in the process.